The Effectivess of Literacy Circles in Encouraging Learners’ Peer Learning and Critical Thinking: A Lesson from Reading Courses - Agus Wismanto; Linda Qiann (Bale Jurnal, 2026)
This study examines the effectiveness of literacy circles in promoting peer learning and critical thinking among Indonesian language learners at the University of PGRI Semarang. Literacy circles, a collaborative learning strategy, are explored as a means to enhance student engagement, encourage deeper analysis of reading materials, and foster meaningful peer interactions. The research employs a qualitative design, utilizing interviews and classroom observations to capture students’ experiences with literacy circles during reading courses. Findings reveal that literacy circles significantly improve critical thinking skills by encouraging students to analyze, evaluate, and synthesize information from diverse perspectives. Peer learning is also promoted, as students engage in reflective discussions that help them clarify misunderstandings and deepen their comprehension. However, challenges such as unequal participation, difficulty in articulating thoughts, and the need for teacher guidance were identified. The study suggests that clear role assignments, structured discussion prompts, and ongoing teacher support are essential for maximizing the effectiveness of literacy circles. The findings contribute to the growing body of research on collaborative learning in reading instruction, offering practical insights for educators seeking to enhance student engagement and cognitive development. The study also highlights the potential of literacy circles to address the limitations of traditional, teacher-centered reading instruction in Indonesian language classrooms.